Ecosystems (Understanding science)
Understanding science is designed to aid instructor in explaining difficult scientific concepts i an easy to understand format. The presenter, Dr. Sceience, brings the central focus to the student in a fun way taht is perfect for introducing basic scientific concepts. The instructor is encouraged to review the program and teacher guides before use in the classroom. Dr. Science demonstrates easy to understand experiments that are highly appropriate for both classroom and home environment. This volume explains ecosystems : relationships of plants, animals & environments, dispersal, barriers, natural community, the biomes, artificial ecosystems and rhythms.